Spontaneous regression of an orbital Langerhans cell histiocytosis after biopsy: A case report. Spontaneous regression of an orbital Langerhans cell histiocytosis - Yahiaoui, Safia; Ghorbel, Asma; Ben Zid, Khadija; Zarraa, Semia; Kchaou, Lina; FidaNoubigh; Kaabia, Wael; Bouguerra, Fadoua; Mousli, Alia; Abidi, Rim; Yousfi, Amani; Nadia, Boujelbene; et al. (Rare tumors, 2022)
Langerhans histiocytosis or Langerhans cell histiocytosis (LCH) is a rare benign pathology representing less than 1% of orbital tumors. It can cause either localized or generalized lesions, leading to the destruction of hard and soft tissues. Eosinophilic granuloma is the most benign form and the predominant clinical presentation of LCH. We report a case of eosinophilic granuloma with orbital involvement in an 18-year-old male patient. Orbital radiotherapy was initially planned, but finally it was not performed due to a spontaneous regression of the lesion after the incisional biopsy. The presented case supports an expectant attitude given the possibility of a spontaneous regression after the biopsy, especially in small lesions. However, long-term follow-up is essential given the risk of recurrence.